Implementation of Project Management office - Malegová, Emília; Říčka, Tomáš; Mayer, Rostislav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2012)
The goal of my thesis is to describe Project management office, its functions; a structure and its place in an organization as well as assumptions for its right implementation in an orgnanization. A first and a second section of the thesis introduce project management and project management office as such. Basic functions and models are described. A third section deals with each stages of implementatation of the office with a particular focus on main analysis and documents. Trends in implementation of the office, main challenges and variables influencing project management office performance are described in fourth section. The informantion was assembled based on studies carried out in the last 7 years. The last section consists of research, analysis and documentation for the first stage of implementation process designed for a specific organization which is the main outcome of the thesis.
Vedoucí práce: Tomáš Říčka
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses